A systematic review of psychosocial outcomes within 2 years of paediatric traumatic brain injury in a school-aged population. (26th August 2013) - Trenchard, Sian Olivia; Rust, Stewart; Bunton, Penny
Abstract: Primary objective : To systematically review the results of investigative research into psychosocial outcomes following paediatric traumatic brain injury (TBI) in children of school-age. Methods : Searches were conducted using PsycINFO, MEDLINE and Science Direct. Three hundred and ninety papers were identified, of which 17 met inclusion criteria. Citation searches uncovered 28 further studies. All 44 studies were appraised in terms of their methodological rigour (e.g. sample characteristics, measures utilized, control groups employed). Results : The papers reviewed described outcomes across domains of behavioural, emotional, adaptive and parent/family functioning. Studies describing behavioural functioning post-injury demonstrated least consistent results. Papers examining emotional, adaptive and parent/family outcomes found that those with head injury presented with poorer functioning than other paediatric populations. Injury severity was commonly identified as a significant predictor of outcome, as were several pre-injury psychosocial factors. Conclusions : Inconsistencies in results may have arisen due to the heterogeneous populations studied and methodologies employed. Research which examines the reliability of assessment measures is needed. Given the high prevalence of difficulties, psychosocial assessment is warranted in this population.